Fabrication and biocompatibility evaluation of hydroxyapatite–polycaprolactone–gelatin composite nanofibers as a bone scaffold - Aminatun, None; Sujak M. K, Aisyah; Izak R, Djony; Hadi, Sofijan; Sari, Yessie Widia; Gunawarman, None; Cahyati, Nilam; Yusuf, Yusril; Che Abdullah, Che Azurahanim (Royal Society of Chemistry, 2024)
One approach to addressing bone defects involves the field of bone tissue engineering, with scaffolds playing an important role. The properties of the scaffold must be similar to those of natural bone, including pore size, porosity, interconnectivity, mechanical attributes, degradation rate, non-toxicity, non-immunogenicity, and biocompatibility. The primary goals of this study are as follows: first, to evaluate hydroxyapatite (HA)/polycaprolactone (PCL)/gelatin nanofiber scaffolds based on functional groups, fibre diameter, porosity, and degradation rate; second, to investigate the interaction between HA/PCL/gelatin scaffolds and osteoblast cells (specifically, the ATCC 7F2 cell line) using in vitro assays, including cell viability and adhesion levels. The fibre samples were fabricated using an electrospinning technique with a 15 kV voltage, a spinneret-collector distance of 10 cm, and a flow rate of 0.3 mL hour−1. The process was applied to five different HA/PCL/gelatin concentration ratios: 50 : 40 : 10; 50 : 30 : 20; 50 : 25 : 25; 50 : 20 : 30; 50 : 35 : 15 (in %wt). Fourier Transform Infrared (FTIR) spectrum analysis and tests revealed no differences in functional groups across the five compositions. The identified functional groups include PO43−, OH−, CO32− and C 00000000 00000000 00000000 00000000 11111111 00000000 11111111 00000000 00000000 00000000 O stretching. Notably, an increase in PCL concentrations resulted in larger fiber diameters, ranging from 369-1403 nm with an average value of 929 ± 175 nm. The highest porosity percentage was (77.27 ± 11.57) %, and a sufficient degradation rate of up to 3.5 months facilitated the proliferation process of osteoblast cells. Tensile strength assessments revealed a significant increase in tensile strength with the addition of PCL, reaching a peak of 1.93 MPa. The MTT assay demonstrated a discernible increase in cell proliferation, as evidenced by increased cell viability percentages on days 1, 3, and 5. Concurrently, the fluorescence microscopy examination indicated an increase in cell numbers, which was especially noticeable on days 1 and 5. The SEM analysis confirmed the biocompatibility of the HA/PCL/gelatin nanofiber scaffold, as osteoblast cells attached and dispersed successfully five days after seeding. Based on these findings, the HA/PCL/gelatin nanofiber scaffold emerges as a very promising candidate for treating bone damage. © 2024 The Royal Society of Chemistry.